OC-080 Low-grade dysplasia in ulcerative colitis: risk factors associated with progression to high-grade dysplasia or colorectal cancer. (22nd June 2015) - Choi, RCH; Ignjatovic-Wilson, A; Rutter, M; Thomas-Gibson, S; Warusavitarne, J; Saunders, B; Graham, T; Hart, AL
Abstract : Introduction: The aim of this study was to identify risk factors associated with development of high-grade dysplasia (HGD) or colorectal cancer (CRC) in ulcerative colitis (UC) patients diagnosed with low-grade dysplasia (LGD). Method: Patients with histologically confirmed extensive UC who were diagnosed with LGD between 1993 and 2012 were identified and followed up to 1 st January 2013. Data on patient demographics, endoscopic and histological variables at the time of the first LGD episode were collected and correlated with progression to HGD or CRC, our primary outcome measure. Time to event analysis was performed using Cox-proportional hazards methods. Results: A total of 172 patients were followed for median of 48 months (interquartile range (IQR), 15–87) who underwent 707 follow-up colonoscopies (median, 4; IQR, 2–6) after the initial LGD episode. Overall, 33 patients developed HGD or CRC (19.1%) during study period. Table 1 shows variables significantly associated with progression to HGD/CRC on univariate analysis. At multivariate level, only macroscopically non-polypoid (HR, 8.6; 95% CI, 3.0–24.8; p < 0.001) or invisible (HR, 4.1; 95% CI, 1.3–13.4; p = 0 .02) lesions, lesions ≥1 cm in size (HR, 3.8; 95% CI, 1.5–13.4; p = 0 .01), and a previous history of indefinite for dysplasia diagnosis (HR, 2.8; 95% CI, 1.2–6.5; P = 0 .01) remained significant contributory factors for developing HGD/CRC. The detection rate for non-polypoid lesions was significantly higher with chromoendoscopy (15.8%) compared with white-light endoscopy (7.8%; p < 0.001). Conclusion: The chromoendoscopy was superior at detecting non-polypoid lesions compared with the white-light endoscopy. Lesions that are large (≥1 cm), non-polypoid, and endoscopically invisible or preceded by "indefinite for dysplasia" diagnosis are independent risk factors for the development of HGD/CRC. Disclosure of interest: None Declared.